Fungsi Penerapan Informed Consent sebagai Persetujuan pada Perjanjian Terapeutik - Rezki Pebrina, Anggun; Najwan, Johni; Alissa, Evalina (Zaaken: Journal of Civil and Business Law, 2022)
This study aims to: Determine the function and role of informed consent in a therapeutic agreement in terms of contract law. As for the formulation of the problem, namely: How is the function and role of informed consent in therapeutic agreements in terms of contract law. Using normative juridical research methods with research approaches used are statutory approaches and conceptual approaches. The results showed that: For doctors, informed consent has a function to provide a sense of security in carrying out medical actions on patients, it can also be used as a means of self-defense against the possibility of claims or lawsuits from patients or their families if the results of medical actions lead to unwanted consequences. Meanwhile, for the patient, informed consent is an embodiment of the patient's right to receive information about the disease he or she is suffering from, what medical action will be taken, the worst possible outcome of the medical action taken, other alternative treatments, and the prognosis. Informed consent also gives patients the freedom to act and make medical decisions for themselves. Abstrak Penelitian ini bertujuan untuk: Mengetahui fungsi dan peran informed consent pada perjanjian terapeutik ditinjau dari hukum perjanjian. Adapun yang menjadi rumusan masalah yaitu: Bagaimana fungsi dan peranan informed consent pada perjanjian terapeutik ditinjau dari hukum perjanjian.Menggunakan metode penelitian yuridis normatif dengan pendekatan penelitian yang digunakan adalah pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Hasil penelitian menunjukkan bahwa: Bagi dokter informed consent memiliki fungsi untuk memberikan rasa aman dalam menjalankan tindakan medis pada pasien, juga bisa dijadikan sebagai alat pembelaan diri terhadap kemungkinan adanya tuntutan atau gugatan dari pasien atau keluarganya bila hasil dari tindakan medis menimbulkan akibat yang tidak diinginkan. Sementara itu, bagi pihak pasien, informed consent merupakan perwujudan dari hak pasien untuk menerima informasi penyakit yang dideritanya, tindakan medis apa yang akan dilakukan, kemungkinan terburuk akibat tindakan medis yang dilakukan, alternatif pengobatan lainnya,serta prognosisinya. Informed consent juga memberi kebebasan bagi pasien untuk bertindak dan2mengambil keputusan medis untuk dirinya sendiri.